2004
DOI: 10.1016/j.femsec.2004.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Homogenous stands of a wetland grass harbour diverse consortia of arbuscular mycorrhizal fungi

Abstract: A molecular approach was applied to investigate the colonisation of arbuscular mycorrhizal fungi (AMF) on the wetland grass Phragmites australis. A PCR assay targeting the traditional families of the Glomeromycota yielded products that were used to construct libraries of 18S rDNA. Five hundred and forty six clones were typed by restriction analysis and 76 representatives were sequenced. The majority corresponded to a wide range of taxa within Glomus group A, a few belonged to the "Diversisporaceae" and none to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
75
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 28 publications
22
75
2
Order By: Relevance
“…This is in accordance with many previous studies reporting that Glomeraceae is the predominant taxon in the roots of various plants (Li et al 2010;Hijri et al 2006;Yamato et al 2008), including those from wetlands (Wirsel 2004;Wilde et al 2009). This seems reasonable since Glomus spp.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with many previous studies reporting that Glomeraceae is the predominant taxon in the roots of various plants (Li et al 2010;Hijri et al 2006;Yamato et al 2008), including those from wetlands (Wirsel 2004;Wilde et al 2009). This seems reasonable since Glomus spp.…”
Section: Discussionsupporting
confidence: 93%
“…The Glomeraceae has been shown to have the ability to colonize new roots via their mycelium or colonized root fragments (Tommerup and Abbott, 1981) and can do so at a higher sporulation rate and intensity than species from Acaulosporaceae and Gigasporaceae (Hart and Reader, 2002). Similar to present study, domination of the AMF communities by Glomus species has also been reported in forest (Husband et al, 2002a,b;Öpik et al, 2003), grassland (Vandenkoornhuyse et al, 2002a;Scheublin et al, 2004;Santos et al, 2006), wetland (Wirsel, 2004) and agricultural (Daniell et al, 2001;Hijri et al, 2006) soils.…”
Section: Amf Diversity In the Temperate Steppesupporting
confidence: 87%
“…This suggests either a site-dependent response to N, or functional diversity within this species. DL-Glo15, which can be assigned to F. mosseae can also be considered a generalist fungal species since it is very common in various ecosystems, including temperate arable fields (Daniell et al, 2001), tropical forests (Husband et al, 2002a,b), seminatural grasslands (Vandenkoornhuyse et al, 2002a) and wetlands (Wirsel, 2004). However, only three sequences of this species were detected in this study, suggesting that this species was exiguous in the research area.…”
Section: Effects Of Fertilization On Amf Abundance and Community Strumentioning
confidence: 67%
“…This previous work and follow-up studies of two distinct genera, Cladosporium and Stagonospora, revealed that at least 30 fungal species colonized healthy P. australis (9,41,42). Our investigations were complemented by a PCRbased study targeting most of the currently known taxa in the Glomeromycota (40), which are the arbuscular mycorrhiza fungi found in the roots of many land plants. Twenty-one putative arbuscular mycorrhiza fungus species were observed within the range theoretically detectable by the approach used.…”
mentioning
confidence: 65%